Pengaruh Penatausahaan Aset Tetap Terhadap Kualitas Laporan Keuangan Pada Satuan Kerja Perangkat Daerah di Kabupaten Bandung - Wini Widiati; Arie Apriadi Nugraha; Ira Novianty (Indonesian Accounting Research Journal, 2021)
The report on the results of the examination of the LKPD Bandung Regency Government in 2018 shows that the administration of fixed assets in the SKPD in the Bandung district government is not yet fully orderly, one of them is because there are fixed assets not known to exist. The purpose of this study was to determine the effect of fixed asset administration on the quality of financial reports. This type of research is a quantitative research with descriptive verification method. The data sources in this study were questionnaires. The population in this study were 63 SKPDs in the Bandung Regency Government. The data analysis method used is descriptive and verificative data analysis. The results of this study show that there remains a positive and significant influence from the administration of fixed assets on the quality of financial statements with an influence rate of 57.4%